Development, scale up, pharmacokinetic and pharmacodynamic evaluation of modified release gliclazide 60 mg tablet formulation produced by direct compression - Elsayed, Tarek Mohamed Ali (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
Background: Gliclazide modified release (MR) tablets are available as innovator brand but it is expensive. It is produced by wet granulation using maltodextrin syrup. Direct compression has the advantage of less processing steps, avoiding degradation of heat and moisture sensitive drugs and reduction of production cost and time. Several factors may affect drug release from MR tablets including the type of polymers and excipients used, their particle size and viscosity grade. Segregation is a common problem encountered during tablet manufacturing by direct compression which makes scale up challenging. Careful selection of excipients is required to avoid this problem. Description of degradation profile of gliclazide in MR tablets is lacking in literature.Objectives: To study factors affecting gliclazide release from tablet formulation in order to successfully develop a modified release gliclazide 60 mg tablet formulation produced by direct compression. Also, to scale up and evaluate stability and bioequivalence of the developed formulation compared to the reference product. Methodology: The effect of different hydrophilic and hydrophobic drug retaining polymers and excipients on gliclazide release was studied. Central composite design was used to study the effect of Methocel® and Maltrin® content on gliclazide release. An optimum formula was selected and a 10,000 tablets batch was produced in IKOP Sdn. Bhd. Stability of the produced tablets were tested according to ASEAN Guidelines on Stability Study of Drug Product. A pilot bioequivalence study was conducted to generate a preliminary data on the in vivo pharmacokinetics of the developed tablet formulation. Results and Discussion: Increasing drug retaining polymer in the tablet resulted in less gliclazide release. The release is slower the higher the viscosity grade or hydrophobicity of the drug retaining polymer. Water insoluble fillers resulted in more controlled release compared to water soluble ones. More significant effect of gliclazide release was associated with maltodextrin particle size compared to molecular size. It was possible to obtain the target gliclazide release profile with the use of Methocel® K100 LV DC2, Supertab® 11 SD and Maltrin® M150 in the tablet formulation. The optimized formulation showed an 80% similarity and 3% difference in dissolution profile when compared to the branded one (Diamicron® MR 60 mg tablet). Increasing Methocel® content reduced gliclazide release at all the time points while Maltrin® M150 exerted a release slowing effect in the first 3 h and release enhancing thereafter. A scale up batch that conforms to compendial requirements of assay, content uniformity and friability, in addition to a dissolution profile within the target was successfully produced. The optimized formulation was stable during a six months accelerated stability study. It showed little change during this storage period and the degradation rate was 0.58% of the labelled content. The dissolution profile also showed little change during this storage period. Impurity A is the major degradation product in the optimized tablet formulation. A pilot study to compare the biopharmaceutical performance of the optimized formulation with the branded product showed close values of pharmacokinetic parameters of both developed and branded formulations. The generic to branded ratios were 1.04, 0.93 and 0.93 for the Cmax, AUC0-t and AUC0-∞, respectively. Conclusion: The developed prototype formulation showed a good stability, in vitro dissolution and in vivo performance similarity with the branded formulation. Further evaluation is required in order to commercialize this generic formulation.